(untitled) (Journal of Bangladesh Institute of Planners, 2016)
Ethics is crucial to the practices of planning theories and concepts as moral judgments and ethical choices encompass planners’ activities. Planners’ ethical values and institutional settings influence their work, but we know very little about these ethical schemes of signification. The article outlines the ethos of working on planning issues and hegemonic ways of thinking about ethics of planning. It presents a fairly brief consideration of what the discourses in ethical planning consist of and also discusses crucial dilemmas of ethics in planning, as these fall in between principles, values, convictions and political and institutional discourses and ideologies. JBIP, Vol. 9, 2016 (Printed in April 2018), pp. 95-112